Depletion of Foxp3+ regulatory T cells but not the absence of CD19+IL‐10+ regulatory B cells hinders tumor growth in a para‐orthotopic neuroblastoma mouse model. Issue 11 (8th September 2022) - Weißenborn, Christine; von Lenthe, Sophie; Hinz, Nicole; Langwisch, Stefanie; Busse, Mandy; Schumacher, Anne; Zenclussen, Ana C.; Fest, Stefan
Abstract: Adaptive immune cells with regulatory function reportedly mediate immune escape in a variety of tumors. Little is known regarding the relevance of the most prominent regulatory cell populations, namely Foxp3+ T regulatory cells (Tregs) and CD19+IL‐10+ B regulatory cells (Bregs), for neuroblastoma (NB) survival. After establishing a novel immunocompetent syngeneic NB mouse model where orthotopic tumors can be generated after intrarenal injection of NB975A cells, we studied the importance of Tregs and Bregs in Foxp3‐DTR mice whose Tregs can be depleted by diphtheria toxin (DT) application as well as in CD19‐specific IL‐10 deficient mice that lack IL‐10+ Bregs (CD19cre +/− × IL‐10 fl/fl mice). We observed Foxp3 Treg cells in tumors from wild type mice. On the contrary, Bregs or B cells were scarce. Specific depletion of Tregs in Foxp3‐DTR mice resulted in an 85% reduction of tumor volume and weight compared to DT‐treated wild type mice and untreated Foxp3‐DTR mice. In contrast, NB tumor growth was not affected in CD19‐specific IL‐10 deficient mice. Similarly, mice lacking mature B cells (μMT mice) and CD19 deficient mice (CD19cre mice) showed no change in growth pattern of NB tumors. In Treg‐depleted mice, reduced tumor growth was associated with an increased concentration of IFN‐gamma, TNF‐alpha, IL‐4, IL‐6, and IL‐10 in isolated splenocytes. In summary, transient ablation of Tregs but not absence of Bregs hindered the growth of NB, strongly suggesting the therapeutic potential of targeting Tregs for this aggressive childhood tumor. Abstract : What's new? While regulatory adaptive immune cells mediate immune escape in a variety of tumors, little is known about their role in neuroblastoma. In a newly‐developed syngeneic orthotopic mouse model, the authors observed that the specific depletion of regulatory T cells in Foxp3DTR knock‐in mice hindered tumor growth and stimulated systemic cytokine production. Neuroblastoma growth was not affected by absence of mature B cells in μMT mice or IL‐10‐producing B cells in CD19cre +/− × IL‐10 fl/fl mice. The findings identified Treg, but not Breg, as a key regulator of tolerance induced by neuroblastoma and an important potential therapeutic target.